Инновации в инженерном образовании методическое пособие - Агранович Б. Л. Борис Львович; Беломестнова Э. Н. Эмилия Николаевна; Дульзон А. А. Альфред Андреевич; Древаль А. Н. Анатолий Николаевич; Иванкина Л. И. Любовь Ивановна; Коваленко А. В. Антонина Владимировна; Козлова Н. В.; Минин М. Г. Михаил Григорьевич; Новикова Е. Г.; Соловьёв М. А. Михаил Александрович; Сафьянников И. А. Игорь Александрович; Стародубцев В. А. Вячеслав Алексеевич (Томск, Изд-во ТПУ, 2009)
В фонде НТБ ТПУ отсутствует